Post Prostate Biopsy Pain: is analgesia essential? - Kyei, M.Y.; Mensah, J.E.; Yeboah, E.D. (Congress of Societe International d’Urologie, Convention Center, 2014)
Introduction and objective: Prostate biopsy continues to form a significant part of day surgeries in urology. Post prostate biopsy pain relief using analgesia is based on the practitioner’s preference. The objective of this study was to establish if there is the need for post prostate biopsy analgesia and to determine the appropriate duration of the analgesia if so used. Materials and Methods: A randomized prospective study of 250 patients scheduled for TRUS biopsy of the prostate from January 2013 to November 2013 was carried out. The patients had 12 core biopsy of the prostate performed with a peri-prostatic block using 2% lignocaine injection. The patients were randomized to; Group 1 (n=64) with a mean age of 67.4 (range 52-82) with no post biopsy administration of analgesia; Group 2 (n=69) mean age of 67.4 (range 40-83) to receive 1g of acetaminophen 8hourly for one day (24 hours) and Group 3(n=117) mean age of 65.9 (Range 45-89) for 2 days (48hours). The parameters documented included the age, TRUS prostate volume, PSA density, the histology of the specimen and the 10 point visual analogue pain scores on post procedure days 1, 2 and 3. Results: Comparing Group 1 with no post biopsy analgesia to Groups 2 with a day (24 hours) and Group 3 with 2 days (48 hours) of analgesia, pain scores on days 1, 2 and 3 were significantly greater for Group 1; p = .0046, p = .0399 and p = .0118 respectively. Comparing Group 2 to Group 3, there was no evidence that pain scores on days 1, 2 and 3 was different between the two groups; p = .1, p = .06, and p = .098 respectively. There was no correlation between the pain scores of the Groups and the age, prostate volume, PSA density and histology of the specimen. Conclusion: Patients given analgesia after TRUS prostate biopsy tend to have significantly lower pain scores on all days than people who receive no pain treatment, thus making the use of analgesia essential. The use of analgesia for 2 days led to relatively lower pain scores compared to one day. There was no evidence to support the use of analgesia beyond day two as most of the patients had no pain by then.
Conference Proceeding
Keywords: Biopsy Pain; Prostate; Analgesia